The savage storm the battle for Italy 1943 - Holland, James 1970- (Atlantic Monthly Press, 2023)
"Acclaimed WWII historian James Holland both narrates and reframes the controversial first months of the Italian Campaign and sets a new standard in the chronicling of war. Following victory in Sicily, while the central command planned the spring 1944 invasion of France, Allied troops crossed into southern Italy in September 1943, expecting to drive Axis forces north and liberate Rome by Christmas. Italy quickly surrendered but German divisions fiercely resisted, and the hoped-for quick victory descended into one of the most challenging and protracted battles of the entire war. Chronicling the dramatic opening months of the Italian Campaign in unflinching and insightful detail, The Savage Storm is unlike any campaign history yet written. Holland has always narrated war at ground level, but here goes further by chronicling events almost entirely through the contemporary eyes of those who were there on all sides and at all levels--Allied, Axis, and civilians alike. Weaving together a wealth of letters, diaries, and other documents--from the likes of American General Mark Clark, German battalion commander Georg Zellner, New Zealand lance-corporal Roger Smith, and legendary war reporter Ernie Pyle-Holland traces the battles as they were experienced across plains, over mountains, through shattered villages and cities, in intense heat and, towards the end of December 1943, frigid cold and relentless rain. Such close-up views persuade Holland to recast important aspects of the campaign, reappraising the reputation of Mark Clark himself and other senior commanders of the U.S. Fifth and British Eighth armies. Given the shortage of Allied shipping and materiel allocated to Italy because of the build-up for D-Day, more was expected of Allied troops in Italy than anywhere else, and, as accounts at the time attest, a huge price was paid by everyone for each bloodily contested mile. [...]"
Keywords: Geschichte 1943; Zweiter Weltkrieg; Italien; World War, 1939-1945 / Campaigns / Italy; World War, 1939-1945 / Italy; Military campaigns; Italy; 1939-1945; Informational works